2006
DOI: 10.1007/s10350-006-0695-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anal Fistula Plug in Closure of Crohn's Anorectal Fistulas

Abstract: Closure of Crohn's anorectal fistula tracts using Surgisis anal fistula plug is safe and successful in 80 percent of patients and 83 percent of fistula tracts. Closure rates were higher with single tracts than complex fistulas with multiple primary openings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
7
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 13 publications
3
109
7
8
Order By: Relevance
“…The results of fibrin glue treatment have been disappointing and the technique has largely been abandoned [12]. Furthermore, treatment is changing, the introduction of the fistula plug has had initial satisfactory results [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The results of fibrin glue treatment have been disappointing and the technique has largely been abandoned [12]. Furthermore, treatment is changing, the introduction of the fistula plug has had initial satisfactory results [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the mesh plug could be used as an adjunct to traditional advancement flap repair or muscle interposition, or possibly it could be used as an initial operation [41] . In a study by O'Connor et al [42] , the use of the fistula plug was studied in patients with Crohn's fistulae (2 with RVF) with an 80% success rate. The success of the two RVF was not specifically addressed.…”
mentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Study design included one RCT56, six prospective cohort studies48 50, 51 54, 55 57 and four retrospective cohort studies14 49, 52 53. In the cohort studies, follow‐up ranged from 0·75 to 29 months after the procedure.…”
Section: Resultsmentioning
confidence: 99%